Las fiestas del dolor: un estudio sobre las celebraciones del Niño Fidencio - Berlanga, José Luis (Fondo Estatal para la Cultura y las Artes de Nuevo León, 1999)
A scholarly anthropological, cultural and religious study of the regional traditional Catholic festival and pilgrimage held twice yearly in the area of Espinoza, N.L